Association Between Resident Race and Ethnicity and Clinical Performance Assessment Scores in Graduate Medical Education. (17th May 2022) - Klein, Robin; Ufere, Nneka N.; Schaeffer, Sarah; Julian, Katherine A.; Rao, Sowmya R.; Koch, Jennifer; Volerman, Anna; Snyder, Erin D.; Thompson, Vanessa; Ganguli, Ishani; Burnett-Bowie, Sherri-Ann M.; Palamara, Kerri
Abstract : Purpose: To assess the association between internal medicine (IM) residents' race/ethnicity and clinical performance assessments. Method: The authors conducted a cross-sectional analysis of clinical performance assessment scores at 6 U.S. IM residency programs from 2016 to 2017. Residents underrepresented in medicine (URiM) were identified using self-reported race/ethnicity. Standardized scores were calculated for Accreditation Council for Graduate Medical Education core competencies. Cross-classified mixed-effects regression assessed the association between race/ethnicity and competency scores, adjusting for rotation time of year and setting; resident gender, postgraduate year, and IM In-Training Examination percentile rank; and faculty gender, rank, and specialty. Results: Data included 3, 600 evaluations by 605 faculty of 703 residents, including 94 (13.4%) URiM residents. Resident race/ethnicity was associated with competency scores, with lower scores for URiM residents (difference in adjusted standardized scores between URiM and non-URiM residents, mean [standard error]) in medical knowledge (−0.123 [0.05], P = .021), systems-based practice (−0.179 [0.05], P = .005), practice-based learning and improvement (−0.112 [0.05], P = .032), professionalism (−0.116 [0.06], P = .036), and interpersonal and communication skills (−0.113 [0.06], P = .044). Translating this to a 1 to 5 scale in 0.5 increments, URiM resident ratings were 0.07 to 0.12 points lower than non-URiM resident ratings in these 5 competencies. The interaction with faculty gender was notable in professionalism (difference between URiM and non-URiM for men faculty −0.199 [0.06] vs women faculty −0.014 [0.07], P = .01) with men more than women faculty rating URiM residents lower than non-URiM residents. Using the 1 to 5 scale, men faculty rated URiM residents 0.13 points lower than non-URiM residents in professionalism. Conclusions: Resident race/ethnicity was associated with assessment scores to the disadvantage of URiM residents. This may reflect bias in faculty assessment, effects of a noninclusive learning environment, or structural inequities in assessment.